Evaluation of intravarietal genetic variability of agronomic traits and stress tolerance in the Portuguese grapevine variety Arinto - Cammisano, Alessandro (2022)
Mestrado em Engenharia de Viticultura e Enologia (Double degree) / Instituto Superior de Agronomia. Universidade de Lisboa / Faculdade de Ciências. Universidade do Porto